The associations of PON1 and APOE polymorphisms with plasma lipid levels and the risk for late complications in type 2 diabetes patients - klen, Jasna; Dolžan, Vita; Goričar, Katja (Journal of Medical Biochemistry, 2023)
Background: Besides good glycemic control, also control of lipid levels can effectively prevent or delay late type 2 diabetes (T2D) complications. As apolipoprotein E (APOE) and paraoxonase 1 (PON1) were shown to suppress atherosclerosis, we investigated the associations of common functional PON1 and APOE polymorphisms with plasma lipid levels and the risk for late complications in T2D patients. Materials and patients: Our retrospective genetic association study included 181 T2D patients genotyped for PON1 rs622, PON1 rs854560, APOE rs429358 and APOE rs7412. Results: PON1 rs622 G allele carriers had significantly lower LDL-C (p=0.024) and lower LDL/HDL ratio (p=0.031) under recessive model. Also in the subgroup of statin treated patients, PON1 rs622 G allele carriers had significantly lower LDL-C (p=0.019), lower total cholesterol/LDL ratio (0.043) and lower LDL/HDL ratio (0.009) when compared to non-carriers. After adjustment for clinical characteristics only associations of PON1 rs622 with macrovascular complications (p=0.002) and MI (p=0.041) remained significant. PON1 rs854560 and APOE genotypes were not associated with late T2D complications. Conclusion: Although our data show some associations between PON1 polymorphisms and lipid levels in T2D patients, as well as with late T2D complications, these associations do not seem to be clinically relevant in T2D patients.